Real-time water quality monitoring system by using wireless UART module / Muhammad Haizrul Fitri Zaini - Zaini, Muhammad Haizrul Fitri (2015)
The water quality plays an important role for everyone. It is not only affecting our ecosystem, but it can also give effect to the living things such as humans, animals and plants. The purpose of this project is to design a real time water quality monitoring using wireless networks. The monitoring system is a system used to determine the state of a parameter on certain times according to the needs. This monitoring system will be implemented at lake, pond and river. The sensor will be used to detect the water quality parameters such as pH and temperature of water. For the real time monitoring purpose, Global System for Wireless UART module is used to enable the system sends the data to the computer. Graphical User Interface (GUI) used to assist the monitoring operator by display the sensor reading on computer screen. The sensor has been tested in few water conditions and gives promising results and accurateness.